SAT0392 The Drug Survival of Anti-Tumour Necrosis Factor (TNF) Treatment in A UK Cohort of Axial Spondyloarthritis Patients. (15th July 2016) - Yahya, F.; Cavill, C.; Berry-Jenkins, J.; Bond, D.; Boyle, C.; Sengupta, R.
Abstract : Background: The use of anti-Tumour Necrosis Factor (TNF) therapy has made a huge impact in the treatment of axial spondyloarthritis (axSpA) patients which include ankylosing spondylitis (AS) and non-radiographic axial spondyloarthritis (nr-axSpA). Patients typically commence these drugs if they fulfil criteria set out by the National Institute for Health Care and Excellence (NICE) guidelines 1 . Continuation of anti-TNF therapy depends on their response, or the occurrence of adverse events (AEs). Current NICE guidelines allow switching to an alternative anti-TNF if side effects occur early in the treatment course. However, few studies have provided data regarding the patterns of drug survival and reasons for discontinuation of anti-TNF in a UK cohort of AxSpA patients 2 . Objectives: To analyse the long-term survival of anti-TNF in AS patients and the reasons for switching anti-TNF therapy in a UK cohort. Methods: We conducted a retrospective analysis of patients who fulfilled AS or nr-axSpA ASAS Classification criteria 3, aged 18 years or above, who received at least one anti-TNF agent at the Royal National Hospital for Rheumatic Diseases (RNHRD) Bath. Data were collected from review of the patients' medical notes. Data included the types and duration of anti-TNF used, and the reasons anti-TNF therapy needed to be stopped or changed. The initial anti-TNF agent prescribed is described as the index treatment. Results: 305 patients, with a mean age of 49.7 (SD12.81), were recruited from the RNHRD AxSpA Biologics database. 261 patients were included in the final data analysis with 90.8% fulfilling the modified New York criteria. Female n=63 (24.1%). The index anti-TNF treatment were Adalimumab n=123 (47.1%), Etanercept n=84 (32.2%), Golimumab n=27 (10.3%), Certolizumab pegol n=15 (5.7%), and Infliximab n=12 (4.6%). 110 (40.4%) patients had to discontinue their index treatment. The most frequent reasons for discontinuation of index anti-TNF included AEs n=36 (36.4%) and loss or lack of efficacy (LOE) n=34 (34.3%). In patients who proceeded to switch to a 2nd anti-TNF, the main reason for stopping the index anti-TNF was AEs n=18 (40%). 26 (57.8%) patients stopped their 2nd anti-TNF treatment with LOE n=12 (46.1%) as the main reason. 6 (23.1%) patients proceeded to have a 3rd anti-TNF with 3 (50%) patients had to stop this completely. Conclusions: About half of the patients had to discontinue their anti-TNF treatment either as an index treatment or subsequent treatment. The most common reason for stopping anti-TNF treatment in our cohort was due to adverse events. 45.5% of patients switched to a second anti-TNF agent and 23.1% of the patients switched from a second to a third anti-TNF agent. References: NICE Technology Appraisal Guidance (TA143): Adalimumab, Etanercept and infliximab for ankylosing spondylitis. 2008. Rosales-Alexander JL, Aznar JB, Pérez-Vicente S, et al.Drug survival of anti-tumour necrosis factor α therapy in spondyloarthropathies: results from the Spanish emAR II Study. Rheumatology 2015; 54 (8):1459–1463. Rudwaleit M, van der Heijde D, Landewé R, et al. The development of Assessment of Spondyloarthritis international Society classification criteria for axial spondyloarthritis (part II): Validation and final selection. Ann Rheum Dis 2009; 68: 777–783. Disclosure of Interest: None declared